VD_FINDINFO HC / 2018 / 697 vom 31. Juli 2018 - VD Tribunal cantonal (2018)
RESPONSABILITÉ DE L'ÉTAT, DOMMAGE, LIEN DE CAUSALITÉ, ENCHÈRES, DOUBLE MISE À PRIX | 41 CO, 42 al. 2 CO, 140 LP, 141 al. 1 LP, 5 al. 1 LP